Identification of stellar-mass black hole binaries and the validity of linear orbital motion approximation in microlensing - Ma, Xiaoyi; Zhu, Wei; Yang, Hongjing (Monthly notices of the Royal Astronomical Society, 2022)
ABSTRACT Gravitational microlensing is unique in detecting binary black (BH) holes with wide (a few au) separations. Models predict that about 1 per cent of microlensing binaries should be due to binary BHs, and yet zero has been robustly identified. Using simulated events with binary BH lenses, we show that the microlensing parallax effect in a typical binary BH event cannot be reliably detected. Given the crucial role of the parallax parameter in determining the mass of dark microlenses, this may explain the non-detection of binary BHs. Additionally, we show that in only a small fraction ($\lesssim 7\ \rm{per\ cent}$) of the simulated events the full orbital motion of the binary lens cannot be modelled with the linear orbital motion approximation. This approximation has been frequently used in modellings of binary microlensing events.